2021
DOI: 10.3390/antibiotics10070841
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Antibacterial Usage during the COVID-19 Pandemic in England, 2020

Abstract: Changes in antibacterial prescribing during the COVID-19 pandemic were anticipated given that the clinical features of severe respiratory infection syndrome caused by SARS-CoV-2 mirror bacterial respiratory tract infections. Antibacterial consumption was measured in items/1000 population for primary care and in Defined Daily Doses (DDDs)/1000 admissions for secondary care in England from 2015 to October 2020. Interrupted time-series analyses were conducted to evaluate the effects of the pandemic on antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 29 publications
6
50
0
5
Order By: Relevance
“…In Portugal, the current pandemic is associated with an immediate decrease in overall antibiotic prescriptions, probably due to mandatory home confinement, social distancing, isolation, and routine use of masks; this trend was not confirmed in the long term (T. M. . A similar trend was observed in England, although antibiotic use in hospitals increased steeply in April 2020 (Andrews et al, 2021).…”
Section: Coronavirus Disease 2019 Pandemic: Further Increase In Ar?supporting
confidence: 70%
“…In Portugal, the current pandemic is associated with an immediate decrease in overall antibiotic prescriptions, probably due to mandatory home confinement, social distancing, isolation, and routine use of masks; this trend was not confirmed in the long term (T. M. . A similar trend was observed in England, although antibiotic use in hospitals increased steeply in April 2020 (Andrews et al, 2021).…”
Section: Coronavirus Disease 2019 Pandemic: Further Increase In Ar?supporting
confidence: 70%
“…Despite the overall trend of decrease in antibiotics usage during 2019–2020. During the first months of the outbreak, a slight increase in prescribing antibiotics was reported in England between March 2020 compared to March 2019 [ 25 ]. Only after, in May 2020, the WHO published guidelines for appropriate usage of antibiotics when managing COVID-19, and increased awareness followed by a decrease in antibiotic use was noted in the primary healthcare setting [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that too few antibiotics were prescribed (e.g., considering a peak in community-acquired bloodstream infections in May 2020 [ 36 ]). Therefore, these fluctuations (including the numbers of prescriptions and consultations) need to be considered when interpreting changes in antibiotic prescribing during the pandemic [ 19 , 21 , 22 , 23 ]. Investigating the appropriateness of antibiotic prescribing against guidelines, antibiotic prescribing in COVID-19/hot hubs and patients’ help-seeking as well as self-management behaviours would also provide helpful insights.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from primary care in England have shown an overall decrease in antibiotic prescribing during 2020 compared to pre-pandemic [18][19][20][21][22][23], with similar trends identified in Scotland [24], Northern Ireland [25] and other countries [26][27][28][29]. However, one study on UK data noted an initial increase in antibiotic prescribing in March 2020 before prescribing levels dropped below those expected (with the lowest rate in May) [20].…”
Section: Introductionmentioning
confidence: 88%